Screening and Evaluation of Actinomycetes B-35 from Rhizosphere of Salvia miltiorrhiza Bunge and Its Biocontrol and Growth-Promoting Effects - Mingli Han; Jing Wang; Hang Lin; Chen Yang; Jing Zhang; Jiawei Liu; Guojun Pan; Na Xiao (Agronomy)
Salvia miltiorrhiza Bunge (S. miltiorrhiza) is one of the most commonly used bulk herbs in China; however, root rot can seriously affect its quality and yields. To minimize the use of chemical pesticides for managing this plant fungal disease, biological control utilizing microbial bio-pesticides offers a promising alternative. This study aimed to enhance the biocontrol resources available for combating S. miltiorrhiza root rot by isolating actinomycetes with antifungal activity from the rhizosphere soil of S. miltiorrhiza and identifying biocontrol actinomycetes with a preventive effect on root rot. A total of 35 actinomycetes were successfully screened from the rhizosphere soil of S. miltiorrhizae. The strain B-35 with the strongest antifungal activity was screened out through antagonizing the pathogen Fusarium solani of S. miltiorrhiza, strain morphology and 16S rRNA analysis. The antagonistic actinomycetes fermentation filtrate and crude extract could significantly destroy the mycelium and spores of Fusarium solani; the biocontrol effect of mature S. miltiorrhiza rhizome reached 83.3%, and the number of leaves, plant height and biomass in the B-35 treatment group were significantly increased compared with the control group. B-35 has a certain application potential in the biological control of root rot and the promotion of S. miltiorrhizae. The antifungal activity of actinomycetes sourced from the rhizosphere soil of S. miltiorrhiza has been demonstrated for the first time, potentially enhancing future crop quality and production.